STUDI KASUS PADA PASIEN RHINOSINUSITIS DENGAN PENERAPAN CUCI HIDUNG DENGAN NACL 0,9% - Isna Aglusi Badri (Lembaga Pengembangan Kinerja Dosen, 2022)
Rhinosinusitis is an inflammatory disease of the nasal mucosa and paranasal sinuses which is usually caused by viral, bacterial, fungal, dental infections, or due to fractures and tumors. Information that states that nasal and sinus disease is ranked 25th out of 50 major disease patterns or about 102,817 outpatients in the hospital. The purpose of this study was to analyze nursing care with the benefit of Nacl 0.9% by washing the nose in rhinosinusitis patients at Embung Fatimah Regional General Hospital Batam City. The discussion compiled in this chapter has been adapted to the stages of the nursing process which includes assessment, nursing diagnoses, nursing interventions, nursing implementation and evaluation or patient progress notes. After being given nursing care to the patient in the form of nasal washing/nasal irrigation using 0.9% NaCl 2 times a day the problem was partially resolved. The patient said that there was a difference before and after irrigation/nasal washing with 0.9% Nacl.